EFEKTIFITAS SENAM LANSIATERHADAP PENURUNAN TEKANAN DARAH PADA KELOMPOK LANSIA HIPERTENSI DI KELURAHAN SUKOHARJO - Purwandari, Kristiana Puji; Suwarno, Siska Ade (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Background: hypertension is a non-comunicable disease or often referred to as the main non-communicable disease but is often found in Indonesia. It is estimated that in 2025 the number of hypertension sufferers will reach 1.5 billion people and 10.4 million people are predicted to die from hypertension and complications. In Indonesia alone 55.2% of hypertension sufferers are dominated by the elderly (Riskesdakes 2018). Hypertension exercise is part of an effort to reduce body weight and manage stress, which are two factors that increase the risk of hypertension (Vitahealth, 2004). Hypertension exercise is one way of maintaining physical fitness or physical exercise that can be done to reduce body weight and manage stress so that it can increase the body's metabolic activity and can stimulate the work of the heart and can strengthen the heart muscles. The purpose of this study was to determine the effect of elderly hypertension exercise on blood pressure in elderly with hypertension in Sukoharjo Village.Methods: This research method used a pre-experimental design method, onegroup pretest-posttest. The number of samples was 30 people who were taken using purposive sampling technique. Data collection by observation of blood pressure before and after the intervention, which was carried out twice a week for four weeks. Blood pressure data were analyzed using paired sample t-test with Î± <0.05.Results: From the results of the study, it can be concluded that the average systolic blood pressure before the elderly hypertension exercise was 151.30 mmHg and the average diastolic blood pressure was 93.83 mmHg. Most of the respondents were classified as Stage 1 hypertension. The average systolic blood pressure after the elderly hypertension exercise was 135.15 mmHg and the average diastolic blood pressure was 90.20 mmHg, which was included in the pre-hypertension classification.